Analisis Hukum terhadap Hak Cuti Haid dan Cuti Melahirkan dalam Praktik Dunia Kerja di Indonesia - Arya Pratama Nazara; Mhd Fadillah Pulungan; Lokot Hasanah Harahap; Rizka Arifah (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study uses qualitative methods to analyze the law on menstrual leave and maternity leave rights in the practice of the workplace in Indonesia. This study aims to examine the implementation of Law Number 13 of 2003 concerning Manpower which provides menstrual leave and maternity leave rights for female workers, and examines the obstacles faced in its implementation in various companies. The results of the study indicate that although the legal framework has clearly regulated these rights, their implementation in the field is still not optimal. The main obstacles found include the lack of understanding and awareness of workers and employers, weak government supervision, and the existence of cultural stigma and discrimination related to menstruation and pregnancy. In addition, several companies still implement policies that are not in accordance with regulations, such as salary deductions or restrictions on leave rights. This study recommends increasing the socialization of regulations, strengthening supervision, and enforcing strict sanctions so that legal protection for menstrual leave and maternity leave rights can be realized fairly and effectively, thereby supporting social justice and the protection of female workers in Indonesia.